Penerapan Model Pembelajaran Berbasis Masalah untuk Meningkatkan Hasil Belajar Materi Statistika di Kelas IX SMP Negeri 30 Medan - Mario Henry Sihotang; Wingston Leonard Sihombing (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2018)
This study aims to (1)  find out whether the application of problem-based learning model can improve students' mathematics learning outcomes on statistical materials, (2) to know how to improve student learning outcomes in statistical materials after being taught by applying problem-based learning model in class IX SMP Negeri 30 Medan. This study is a classroom action research conducted in 2 cycles, each cycle is implemented in 3 meetings. Subjects in this study were students of class IX-7 SMP Negeri 30 Medan academic year 2017/2018 which amounted to 34 people. Based on the results of the diagnostic tests are known low student learning outcomes with an average grade grade of 55.58. After giving the action in cycle I by applying Problem-Based Learning Model, student's classical learning completeness level is medium with average score 70,14 with 22 student or 64,7% from all student have reach learn masculinity and ability of teacher to manage learning is 2, 44 with good category. Furthermore, after the implementation of the action in cycle II, the student's classical learning completeness is high with the average grade grade 80,3 where the number of students who have achieved mastery of learning as many as 30 students or 88,23% of all students and the ability of teachers to manage learning is 3,21 with very good category. Based on the results of this study can be concluded that Problem-Based Learning Model can improve student learning outcomes on the subject of statistics in class IX-7 SMP Negeri 30 Medan in the academic year 2017/2018.Keywords: Learning Outcomes, Problem Based Learning Model, Statistics.